1994
DOI: 10.1111/j.1651-2227.1994.tb13154.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation increases growth velocity of male children and adolescents with short stature

Abstract: We assessed the effect of zinc supplementation on growth velocity in 79 children and adolescents (48 males, 38 females) with idiopathic short stature. Their height-for-age was < 5th percentile (NCHS standards) and their weight-for-age was normal. Patients were assigned randomly to a supplemented group (S) to receive Zn 10 mg/day or to a placebo (P) group, according to gender and age, and were followed-up for 12 months using a double-blind design. Weight, height, armspan, length of lower segment and plasma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 21 publications
1
34
2
2
Order By: Relevance
“…Growth can also be disturbed by deficiencies in minerals and vitamins. It was found that in the group of short stature children, zinc intake was less than 2/3 of daily demand, and zinc supplementation resulted in the acceleration of growth in boys with short stature when the cause is not determined [15]. In the presented study, the average content of zinc concentration in the blood, plasma, and urine in children with short stature was significantly lower than that in the control group.…”
Section: Discussioncontrasting
confidence: 77%
“…Growth can also be disturbed by deficiencies in minerals and vitamins. It was found that in the group of short stature children, zinc intake was less than 2/3 of daily demand, and zinc supplementation resulted in the acceleration of growth in boys with short stature when the cause is not determined [15]. In the presented study, the average content of zinc concentration in the blood, plasma, and urine in children with short stature was significantly lower than that in the control group.…”
Section: Discussioncontrasting
confidence: 77%
“…In several zinc supplementation studies (Walravens & Hambidge, 1976;Walravens et al, 1983;Gibson et al, 1989;Castillo-Duran et al, 1994) in which growth but not body composition was measured, positive responses in terms of height and=or weight gain have been reported in the supplemented compared to the placebo children. Less consistent positive effects on growth have been observed in vitamin A or iron supplementation studies (Angeles et al, 1993;Lawless et al, 1994;Bahl et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to comment that zinc supplementation may show a positive effect on growth of adolescent children if the sample size was larger. Castillo-Durán et al (1994) have reported an increased growth velocity in males with 10 mg of zinc supplementation for 12 months to pre-adolescent and adolescent children. In a randomized control trial among Zimbabwean school children of 11-17 years of age (Friis et al, 1997), two Abbreviations: BMI, body mass index; HAZ, height-for-age z score; WAZ, weight-for-age z score.…”
Section: Effect On Anthropometrymentioning
confidence: 99%